Meeting the requirements of the Mega Free Trade Agreement on Standardization: gaps on policy implementation - Anh, Nguyen Quynh; Quynh Trang, Nguyen Ha Thi; Hong, Pham Van; Bich Phuong, Nguyen Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
The Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) and the Free Trade Agreement between Vietnam and the European Union (EVFTA) are two new generation free trade agreements which are setting a high standard and being comprehensive for global trade. In terms of trade freedom, they differ from the traditional trade agreements that Vietnam has ratified. To carry out these two Agreements, the Vietnam’s Government issued Decission No. 121 / QD-TTg, dated 24th January 2019, to approve the implementation plan of the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) and Decision No. 1201 / QD-TTg, dated 6th August 2020 to approve the implementation plan of the Free Trade Agreement between Vietnam and the European Union (EVFTA). These two decisions set out revising institutions and policies related to standardization, focusing on coordinating responsibility for standards development and conformity assessment to match these two free trade agreements’ requirements. The article first analyzes the CPTPP and EVFTA’s requirements for standardization, then refers to the respective policies of Vietnam to find the gaps in developing and implementing policies related to standards. In addition, the recommendations to improve policy gaps and to ease the harmonization of standards between the international and Vietnam are proposed. Code: 20122001